2010
DOI: 10.3390/w2040849
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization of SWAT Model Parameters for Use in Ungauged Watersheds

Abstract: There has been a steady shift towards modeling and model-based approaches as primary methods of assessing watershed response to hydrologic inputs and land management, and of quantifying watershed-wide best management practice (BMP) effectiveness. Watershed models often require some degree of calibration and validation to achieve adequate watershed and therefore BMP representation. This is, however, only possible for gauged watersheds. There are many watersheds for which there are very little or no monitoring d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 33 publications
(44 reference statements)
1
48
0
1
Order By: Relevance
“…These comparisons for the three regionalization approaches used in this study show that the median values were considered unsatisfactory for both the calibration and validation watersheds, and compared poorly with the results obtained by Gitau and Chaubey [13] and Parajka et al [12] It may be said that none of the three approaches used in this investigation gave even marginally satisfactory results, based on both the NSE and PBIAS test statistics. Of the three methods, only two calibration and two validation watersheds were considered satisfactory for the regional average approach, none was considered satisfactory for the nearest neighbor approach, and only one calibration watershed was considered satisfactory for the donor approach.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…These comparisons for the three regionalization approaches used in this study show that the median values were considered unsatisfactory for both the calibration and validation watersheds, and compared poorly with the results obtained by Gitau and Chaubey [13] and Parajka et al [12] It may be said that none of the three approaches used in this investigation gave even marginally satisfactory results, based on both the NSE and PBIAS test statistics. Of the three methods, only two calibration and two validation watersheds were considered satisfactory for the regional average approach, none was considered satisfactory for the nearest neighbor approach, and only one calibration watershed was considered satisfactory for the donor approach.…”
Section: Discussionmentioning
confidence: 62%
“…Test results from this study were compared to results from two previous studies (Gitau and Chaubey [13] and Parajka et al [12] For the present study, median NSE values for monthly streamflow using the regional average approach were 0.40 and 0.28 for the source and validation watersheds, respectively. The median NSE value for monthly streamflow was 0.69 for calibrated watersheds used in the study by Gitau and Chaubey, [13] while the median daily streamflow NSE values for calibrated and validated values were 0.61 and 0.56 in the study performed by Parajka et al [12] In the comparison of the nearest neighbor approach in this study, median monthly NSE values were -0.07 and 0.05 for the source and validated watersheds, respectively, while Parajka et al [12] reported median daily NSE values of 0.66 and 0.61, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations